The Economic Implications of Skill Mismatch in China’s Labor Market: A Focus on Higher Education Graduates - Tianqi Shi (Law and Economy, 2024)
Skill mismatch in China’s labor market has become a growing concern, particularly for higher education graduates. This paper explores the economic implications of skill mismatches, focusing on sectors such as high-tech and manufacturing, which are vital for China’s economic growth and global competitiveness. It examines the productivity losses resulting from skill mismatches and evaluates government policies aimed at addressing these challenges, including vocational training reforms and regional strategies. The paper also proposes strategies for aligning education more closely with labor market needs, emphasizing collaboration between educational institutions and industries, flexible learning pathways, and the use of emerging technologies. By addressing these mismatches, China can enhance its workforce’s adaptability and productivity, ensuring sustained economic growth and competitiveness in the global market.